1997
DOI: 10.1016/s0008-6363(96)00260-x
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion-induced changes in cardiac contractility and oxygen consumption are not endothelium-dependent

Abstract: The results suggest that the arterial endothelium is not involved in the Gregg phenomenon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
22
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 17 publications
3
22
0
Order By: Relevance
“…The increase of F dev , which results from a change from low to high P perf (Gregg effect), has been reported several times in literature (1,14,15,17,18,39). Recently, we showed in perfused rat papillary muscle that the Gregg effect, which is accompanied by an increase in muscle diameter (transversal stretch), was initiated by activation of Gd 3ϩ -sensitive SACs (31) -sensitive positive inotropic mechanism is active.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…The increase of F dev , which results from a change from low to high P perf (Gregg effect), has been reported several times in literature (1,14,15,17,18,39). Recently, we showed in perfused rat papillary muscle that the Gregg effect, which is accompanied by an increase in muscle diameter (transversal stretch), was initiated by activation of Gd 3ϩ -sensitive SACs (31) -sensitive positive inotropic mechanism is active.…”
Section: Discussionmentioning
confidence: 78%
“…From the literature, it is known that SACs could be located on the sarcolemma or t-tubular system of the cardiomyocytes (45); however, SACs have also been found on the vascular (33) or endocardial (24,27) endothelium. Dijkman et al (16)(17)(18) showed that perfusion-induced changes in contractility were related to Fig. 2.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The membrane deformation changes ion fluxes through SACs, resulting in increased cardiac contractility. This hypothesis is supported by the findings that the Gregg response was related to capillary perfusion (13,15) and changes in coronary vascular volume (3), but was not related to arterial endothelium or its released inotropic substances (12,14,32,33). The identity of the coronary perfusion-induced increased cation influx is not yet clear and needs further experiments.…”
Section: Discussionmentioning
confidence: 80%
“…An increase in coronary perfusion with a concomitant increased filling of the coronary vessels leads to an increase in cardiac contractility and cardiac oxygen consumption known as the Gregg effect (1,3,14,18,22,36). Filling of the coronary vessels will change hoop (circumferential) stress in the vessel wall, thereby mechanically deforming the membranes of myocardial cells.…”
mentioning
confidence: 99%